Cognitive navigation: A phenomenological study of prospective elementary school teachers’ experiences in managing cognitive overload in blended learning - Faridl Musyadad; Kassymova Gulzhaina Kuralbayevna; Atika Dwi Evitasari; Garib Firman Buaga (Universitas Negeri Surabaya, 2026)
The digital transformation in higher education has established blended learning as a permanent pedagogical paradigm, yet it has created a paradox in which instructional flexibility often leads to increased cognitive complexity for students. This study aims to explore the lived experiences of Elementary School Teacher Education students in navigating cognitive overload and to identify adaptive strategies employed to maintain learning effectiveness in a blended learning environment. Using a qualitative-phenomenological design, this study involved active students at IKIP PGRI Wates who had completed at least one semester of blended learning. Data were collected through semi-structured in-depth interviews and reflective learning journals, which were then analyzed using an inductive thematic approach. The findings reveal that cognitive overload is primarily triggered by fragmented instructional design, technical friction between platforms, and unmanaged dual task demands. These factors led to a degradation in the quality of cognitive processing, shifting students’ orientation from deep conceptual understanding toward a pragmatic, administrative focus. However, these findings also highlight the crucial role of Self-Regulated Learning as a metacognitive resilience mechanism that mitigates the impacts of mental fatigue and academic stress. This study concludes that cognitive overload in blended learning is a multidimensional phenomenon that requires coherent instructional synchronization and systematic support for students’ self-regulation. The practical implications of this study emphasize the need for platform standardization and the integration of metacognitive training as crucial navigational tools for prospective elementary school teachers to ensure their cognitive resilience in implementing learning technologies in the future.